Membangun Budaya Literasi Digital Bahasa Arab melalui Platform E-Learning - Mahmudi A. R. (Multiverse: Open Multidisciplinary Journal, 2025)
In the era of digital transformation, literacy extends beyond the ability to read and write printed texts to encompass competencies in navigating, evaluating, and producing information in cyberspace. This study examines strategies for fostering a culture of Arabic digital literacy through the integration of e-learning platforms in higher education. The research addresses the question of how instructional technology can simultaneously enhance Arabic language proficiency and cultivate critical awareness toward digital Arabic content. Employing a qualitative approach based on literature review and conceptual analysis, the study synthesizes recent scholarship on digital literacy, language pedagogy, and technology-enhanced learning. The findings indicate that integrating Arabic language curricula with interactive e-learning features—such as multimedia resources, collaborative forums, adaptive assessments, and digital content production tasks—can create an adaptive and sustainable learning ecosystem. Such integration not only strengthens linguistic competence across reading, writing, listening, and speaking skills, but also promotes critical engagement, information filtering skills, and ethical digital participation. The study argues that developing Arabic digital literacy requires a systematic alignment between pedagogical design, technological affordances, and cultural-contextual relevance to ensure meaningful and responsible digital engagement.